Light Wave Propagation Model for Indoor Visible Light Communication Systems Employing Small LED Sources - Elsaaty, Marwa M. A.; Zaghloul, Adel; Hussein, Khalid. F. A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The aim of the present work is to build a robust and computationally efficient model for the light wave propagation in indoor visible light communication (VLC) systems. It is assumed that a small (point) LED source is used inside a room of relatively small dimensions (room area ≤ 5m × 5m). The light wave is treated as an electromagnetic wave suffering multiple reflections on the walls of the room. The Geometrical Theory of Diffraction (GTD) is applied for evaluation of the light wave reflection on the rough walls of the room. Also, the present work is concerned with developing a new computational method for the assessment of intersymbol interference (ISI) encountered in such indoor VLC systems. The signal strength, the power of ISI, and hence, the signal-to-ISI ratio (SISIR) are evaluated over the horizontal plane of the mobile units (at a height of about 1m above the room floor). The effects of the room dimensions and some structural parameters such as the reflectance of the side walls on the SISIR are numerically investigated.